Clinical features and molecular genetics of patients with ABCA4‐retinal dystrophies. Issue 5 (30th November 2020) - Holtan, Josephine Prener; Aukrust, Ingvild; Jansson, Ragnhild Wivestad; Berland, Siren; Bruland, Ove; Gjerde, Birgitt Løkhaug; Stokowy, Tomasz; Bojovic, Ognjen; Forsaa, Vegard; Austeng, Dordi; Rødahl, Eyvind; Bredrup, Cecilie; et al.
Abstract: Purpose: Pathogenic variations in the ABCA4 gene are a leading cause of vision loss in patients with inherited retinal diseases. ABCA4–retinal dystrophies are clinically heterogeneous, presenting with mild to severe degeneration of the retina. The purpose of this study was to clinically and genetically characterize patients with ABCA4‐retinal dystrophies in Norway and describe phenotype–genotype associations. Methods: ABCA4 variants were detected in 111 patients with inherited retinal disease undergoing diagnostic genetic testing over a period of 12 years. In patients where only a single ABCA4 variant was found, whole‐gene ABCA4 sequencing was performed and intronic variants were investigated by mRNA analyses in fibroblasts. Medical journals were used to obtain a clinical description and ultrawidefield autofluorescence images were used to analyse retinal degeneration patterns. Results: The genetic diagnostic yield was 89%. The intronic splice variant c.5461‐10T>C was the most prevalent disease‐causing variant (27%). Whole‐gene ABCA4 sequencing detected two novel intronic variants (c.6729+81G>T and c.6817‐679C>A) that we showed affected mRNA splicing. Peripheral retinal degeneration was identified in 33% of patients and was associated with genotypes that included severe loss of function variants. By contrast, peripheral degeneration was not found in patients with a disease duration over 20 years and genotypes including p.(Asn1868lle), c.4253+43G>A or p.(Gly1961Glu) in trans with a loss of function variant. Conclusion: This study demonstrates the clinical and genetic heterogeneity of ABCA4‐retinal dystrophies in Norway. Further, the study presents novel variants and increases our knowledge on phenotype–genotype associations and the presence of peripheral retinal degeneration in ABCA4‐retinal dystrophy patients.